Penerapan Model Pembelajaran Model Pembelajaran Student Facilitator And Explaining Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas V Sekolah Dasar Negeri 164 Pekanbaru - ines yuwan dari (el-Ibtidaiy:Journal of Primary Education, 2019)
This research aimed at increasing student learning achievement on Mathematics subject throughthe implementation of Student Facilitator and Explaining learning model at thefifth grade of State Elementary School 164 Pekanbaru.  It was instigatedby the low of student learning achievement that could not pass the minimum standard of passing grade determined 75.  It was a Classroom Action Research.  The subjects of this research were the teachers and students.  The objects were Student Facilitator and Explaining learning model and learning achievement.  This research was conducted for two cycles, and every cycle comprised two meetings.  Observation, learning achievement test, and documentation were the techniques of collecting the data.  The technique of analyzing the data was Descriptive qualitative with percentage.  Based on the research findings and data analyses,Student Facilitator and Explaining learning model could increase learning achievement.  It could be seen from student learning achievement that the mean was 68.61 before the action with 47.22% classical mastery, and it was on poor category.  After implementing Student Facilitator and Explaining learning model in the first cycle, student learning achievement mean increased to 73.88 with 66.66% classical mastery, and it was on enough category.  In the second cycle, student learning achievement mean increased to 80.27with 86.11% classical mastery, and it was on perfect category.  Thus, Student Facilitator and Explaining learning model achieved success indicators that were expected at thefith grade of state of student school 164 Pekanbaru.